Evidence-based, interdisciplinary guidelines for anti-inflammatory treatment of uveitis associated with juvenile idiopathic arthritis - Heiligenhaus, Arnd; Mackensen, Friederike (Rheumatology international, 2011)
Uveitis in juvenile idiopathic arthritis (JIA) is frequently associated with the development of complications and visual loss. Topical corticosteroids are the first-choice therapy, and immunosuppression is commonly used. However, treatment has not been standardized. Representatives from the German Ophthalmological Society, Society for Childhood and Adolescent Rheumatology, and the German Society for Rheumatology reached consensus on a standardized treatment strategy according to disease severity in the individual patient. The recommendations were based on a systematic literature analysis in MEDLINE and consensus expert meetings. Evidence and recommendations were graded, and an algorithm for anti-inflammatory treatment and final statements confirmed in a Delphi method. An interdisciplinary, evidence-based treatment guideline for JIA uveitis is presented.
Gesehen am 17.04.2018